Klebsiella pneumoniae in vegetable products: antimicrobial resistance and consumer health risk. (20th October 2021) - Centorotola, G; Cornacchia, A; Marfoglia, C; Saletti, MA; Ciarrocchi, A; Del Matto, I; Galante, D; Rodrigues, C; Brisse, S; Pomilio, F
Abstract: Background: Klebsiella pneumoniae (Kp) is considered one of the major causes of human hospital infections. Moreover, Kp is often present in several food products and it could be a potential health hazard for the consumers through the increase of Kp antimicrobial resistance (AMR) to the main routinely used antibiotics classes. The aim of this study was to evaluate the AMR profile of Kp strains isolated from vegetable food products. Methods: The whole genome sequences of 10 Kp strains, previously isolated from carrots (n. 4), salads (n. 3), tomatoes (n. 2) and pumpkin (n. 1) samples, were obtained by next generation sequencing technique, using Illumina platform. Phenotypic and genotypic AMR profiles, with particular attention to β-lactams, quinolones and aminoglycosides resistances, were acquired by both agar diffusion and micro-dilution susceptibility testing and uploading the Kp sequences to Institut Pasteur platform (https://bigsdb.pasteur.fr/ ), respectively. Results: Most of Kp strains (9 of 10) resulted susceptible to the main antibiotics tested and few AMR genes were detected in silico besides the native blaSHV, blaOKP and blaLEN. Only one Kp harboured blaAMPC and blaCMY, showing resistance to 5 β-lactams (amoxicillin/clavulanate, cefoxitin, cefpodoxime, cefpodoxime/clavulanate, ceftobiprole). Regarding the quinolone resistances, all the Kp strains carried gyr and par genes. No aminoglycoside resistance genes were highlighted in the 10 Kp strains studied. Conclusions: These preliminary results showed the presence, in vegetable foods, mainly in ready to eat raw products, of Kp strains, harbouring no or few AMR genes. Good hygiene practices should be properly applied during the entire food processing chain, to avoid hazardous implications for the consumer. Further studies are needed in order to: analyse more vegetable samples, deeply evaluate the phenotypic and genotypic AMR profile of the Kp strains and their possible transmission from food products to consumer. Key messages: Klebsiella pneumoniae is often isolated in food, as ready to eat vegetables, and it could be a potential public health risk due to the antimicrobial resistance increase to main antibiotics. The presence of Klebsiella pneumoniae in food implies the correct application of good hygiene practices in the entire food processing chain, in order to avoid dangerous effects for consumers.